Relationship between antibiotic residues and occurrence of resistant bacteria in Nile tilapia (Oreochromisniloticus) cultured in cage-farm - Monteiro, Sergio H.; Garcia, Fabiana; Gozi, Katia S. [UNESP]; Romera, Daiane M.; Francisco, Jeane G.; Moura-Andrade, Graziela C. R.; Tornisielo, Valdemar L. (Taylor & Francis Inc, 2016)
The aim of this study was to investigate the relationship between antibiotic residues found in the muscle of cage-farm-raised Nile tilapia (Oreochromisniloticus), the occurrence of resistant bacteria, and the sanitary practices adopted by farmers in Ilha Solteira reservoir, Brazil. Nine fish (three small fish, 40-200 g; three medium-sized fish, 200-500 g; and three large fish, 500-800 g) were collected from four cage farms every three months from April 2013 to January 2014. Ten antibiotic residues were determined using liquid chromatography-mass spectrometry, and bacteria were isolated and tested for antibiotic resistance to determine the multiple antibiotic resistance (MAR) index. Only three antibiotics (oxytetracycline, tetracycline, and florfenicol) were detected in the muscle of Nile tilapia, and their residues were the highest in small fish; however, the MAR index was higher in large fish. In addition, a direct positive relationship between the MAR index and the concentration of antibiotic residues in Nile tilapia was found. Overall, the adoption of prophylactic management practices improved the sanitary status of cage farms, reducing bacterial infections and hampering the development of antibiotic-resistant bacteria.
Keywords: Cage farming; MAR index; LC-MS/MS; reservoir; antibiotic resistance